Are there long-term benefits from early childhood education in low- and middle-income countries? - M. Najeeb Shafiq; Amanda Devercelli; Alexandria Valerio (Arizona State University, 2018)
We examine the relationship between participation in early childhood education (ECE) and various long-term outcomes: post-ECE educational attainment, the development of both cognitive and socioemotional skills, and labor market outcomes. The data are from the recent Skills Toward Employability and Productivity surveys of urban adults in 12 low- and middle-income countries. Using OLS regression and propensity score matching techniques, we find suggestive evidence of long-term benefits across countries, as well as mixed evidence within countries. Notably, we find positive and statistically significant associations between ECE participation and post-ECE educational attainment (a mean of 0.9 additional years across countries). We find relatively fewer cases of positive associations between ECE and long-term socioemotional outcomes. The evidence on ECE and labor market outcomes is varied, with positive associations for skill-use but weak associations with earnings. Such mixed results suggest that improvements in the quality of ECE programs are necessary for realizing the full range of long-term benefits.